Gender norms associated with adolescent sexual behaviors in Uganda - Nalukwago, Judith; Crutzen, Rik; Borne, Bart van den; Mukisa Bukuluki, Paul; Bufumbo, Leonard; Burke, Holly McClain; Field, Samuel; Zikusooka, Amos; Fiedler, Anne Akia; Alaii, Jane (International Social Science Journal, 2019)
Gender norm attitudes and practices remain deeply entrenched in many African societies (Gibson et al. 2014; Wight et al. 2006). Countries driven by gender inequalities that constrain Judith Nalukwago, the lead author of this article, has a PhD in Public Health from the Faculty of Health, Medicine and Life Sciences of Maastricht University, The Netherlands. She is a health promotion scholar, practitioner and a behavioural scientist with grounded skills in both theoretical and practical implementation of social and behaviour change interventions. She has a background in monitoring, evaluation, research, learning/ knowledge management, and adolescent health programming from an academic and programme implementation perspective. Email: j.nalukwago@maastrichtuniversity.nl individual behaviour in sexual interactions often have the highest rates of HIV and teenage pregnancies (Hardee et al. 2014; Richards et al. 2013; Van den Berg et al. 2013). Women and girls face more gendered risks than their male counterparts, which affects their social, economic and political opportunities (Mbonye et al. 2012; UNAIDS 2016; UNICEF 2015)
Keywords: Gender norms; Adolescent sexual behaviors; Uganda